The Combined Effect of Physical Activity and Alcohol Consumption on Life Satisfaction in Adolescence - Breki Steinn Mánason 1991- (2014)
Prior research on life satisfaction in adolescence has focused on the effects of alcohol consumption and physical activity separately but not collectively. The objective of this study was to find out the effects of lifetime alcohol consumption and physical activity on life satisfaction in adolescents. Another objective was to find out whether the impact of alcohol on life satisfaction was dependent on physical activity. Data was used from a sample of 1,986 Icelandic students from a cross-sectional survey conducted by the Icelandic Centre for Social Research and Analysis (ICSRA) in 2004. The survey was conducted in every high school in Iceland. A 3 alcohol consumption (Never, 1-19 times and 20 times or more) x 3 physical activity (Less than once a week, 1-3 times a week and 4 or more times a week) factorial ANOVA was used to test the hypotheses. The results showed that the participants who engaged in physical activity more frequently had higher life satisfaction than those who engaged in physical activity less frequently. The participants who had consumed alcohol on many occasions had lower life satisfaction than the ones who had done so on fewer occasions. The impact of alcohol consumption on life satisfaction was not dependent on physical activity. Fyrri rannsóknir á lífsánægju unglinga hafa sýnt fram á áhrif áfengisneyslu annars vegar og líkamlegrar virkni hins vegar en lítið er til af rannsóknum um sameiginleg áhrif þessara breyta. Markmið þessarar rannsóknir var að skoða áhrif áfengisneyslu yfir ævina og líkamlegrar virkni á lífsánægju unglinga og þá sérstaklega hvort að áhrif áfengisneyslu væru breytileg eftir líkamlegrar virkni. Notuð voru fyrirliggjandi gögn úr rannsókninni Ungt fólk 2004 sem framkvæmd var af Rannsóknum og greiningu (the Icelandic Centre for Social Research and Analysis). Úrtakið samanstóð af 1986 íslenskum unglingum í framhaldsskóla. Rannsóknin var framkvæmd í öllum framhaldsskólum landsins. 3 áfengisneysla yfir ævina (Aldrei, 1-19 sinnum og 20 sinnum eða oftar) X 3 líkamleg virkni ...